The Role of Soft Law in the Application of the Law: The Norwegian Perspective - Frode Elgesem (Oslo Law Review)
The article explores whether soft law instruments—such as the UN Guiding Principles on Business and Human Rights (UNGP) and OECDʼs Guidelines for Multinational Enterprises (OECD Guidelines)—have a role to play in the application of Norwegian law. One significant development is that these standards are now being transposed into hard law, as the Norwegian Transparency Act does, thus introducing new, legally binding standards for the companiesʼ business conduct based on the said soft law instruments. Within the scope of the relevant legislation, soft law thus plays a significant role in the application of the law. Through the Transparency Act, the impact of soft law is especially powerful, since also future developments of the OECD Guidelines shall be taken into account in the Actʼs application. The article argues that soft law instruments like the UNGP and OECD Guidelines may also play a role in the application of the law in other fields of company-related law, such as in the application of the principle of liability of a parent company for acts committed by its subsidiaries (in Norwegian: ‘ansvarsgjennombruddʼ), the law of torts and the question of a companyʼs liability for harmful acts against third parties, especially an employerʼs liability for acts of employees (in Norwegian: ‘arbeidsgiveransvarʼ) and a the companyʼs liability for acts of its governing bodies and leading decision makers (in Norwegian: ‘organansvarʼ), and, in criminal law, whether a companyʼs faithful implementation of the UNGP and OECD Guidelines could be a defense against corporate criminal liability for human rights abuses committed by personnel acting on behalf of the company. There may be some reluctance in the application of the soft law principles in a legal context, but it must be expected that the transposition of the UNGP and OECD Guidelines into hard law through the Transparency Act, and the ensuing legal obligations for larger Norwegian companies and their boards, have will notably increase the potential impact of these soft law instruments on the hard law in Norway.